Stories Rather than Surveys: A Journey of Discovery and Emancipation - Elizabeth Kendall PhD (International Journal of Qualitative Methods, 2013)
Empirical research, which has traditionally been privileged in Western health disciplines, has left notable gaps in the implementation of health interventions for Indigenous people and in the knowledge of and respect for Indigenous ways of knowing, both locally and globally. This article emphasizes the notion of pluralism in health research, and the responsibility of non-Indigenous researchers to collaborate respectfully and at a personal level with Indigenous people. It explores the value of unexpected forms of knowledge, and the need to recognize the stories and narratives of research participants as valuable in themselves, rather than as something to be dissected or reinterpreted out of context. Through the exploration of one data collection experience, we show how research collaboration, negotiation, and respect can transcend the boundaries between Indigenous and non-Indigenous people, researchers and non-researchers, those with and without disabilities, and between countries.